Effect of ball mass on dribble, pass, and pass reception in 9-11-year-old boys' basketball - Arias, J. L.; Argudo, F. M.; Alonso, J. I. (Research Quarterly for Exercise and Sport, 2012)
The objective of the study was to analyze the effect of ball mass on dribble, pass, and pass reception in real game situations in 9-11-year-old boys' basketball. Participants were 54 boys identified from six federated teams. The independent variable was ball mass, and dependent variables were number of dribbles, passes, and pass receptions. Three situations were established in which the participants played four games with each of the following: (a) regulation ball (485 g, 69-71 cm), (b) ball of smaller mass (440 g, 69-71 cm), and (c) ball of greater mass (540 g, 69-71 cm). Four observers recorded data from observing game videos using a computerized register instrument. Participants executed more dribbles, passes, and pass receptions with the 440-g ball when compared to the regulation (p < .05) and 540-g ball (p < .01). Reduction of ball mass seems to have enabled the children to go from paying attention to aspects related to ball handling to aspects of game interpretation.